Enseignement de la philosophie et enseignement des faits religieux en France: entre exigence de la liberté de penser et nouveaux enjeux pédagogiques - Gaudin, Philippe (Zeitschrift für Religionskunde, 2016)
Reconciling respect for the convictions of pupils and families with the teaching of philosophy raises new problems nowadays, because secondary education has become largely “massified” and, like other European countries, France is experiencing both an advanced secularisation and a new cultural and religious plurality. While “religion” as a concept has long been “part of the curriculum” for philosophy, there is a need to analyse the reasons for the reluctance of philosophy teachers to teach about religions. But a simple analysis of the philosophy curricula and of the list of officially recognised authors shows how strongly present religion is in philosophy. In other words, whatever their own fundamental philosophical options, teachers cannot avoid initiating their pupils into a whole cultural background that is nowadays most often lacking.